PENANAMAN NILAI KARAKTER GEMAR MEMBACA - Puput Purwita Sari (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
The reading interest of Indonesian people today is still low, especially among school-age children. The low reading interest of students is influenced by many things, such as lack of direction from parents, lack of guidance by teachers at school, unavailability of books which obstructs students' reading interest. Therefore, there should be more attention given to the efforts to increase students' reading interest, which is by implementing reading interest character value. Implementing reading interest character value can be started from a school environment which definitely involves all components of the school, so that between principals, teachers, students and school libraries must work together. Implementing reading interest character value can be done using several methods including habituation, example, routine activities, spontaneous activities and conditioning. Keyword: reading interest character value